2019
DOI: 10.4142/jvs.2019.20.e46
|View full text |Cite
|
Sign up to set email alerts
|

Salivary alpha-amylase as a stress biomarker in diseased dogs

Abstract: Salivary alpha-amylase (sAA) is a stress biomarker in human diseases, but there are no reports of sAA measurements in diseased dogs. This study measured the sAA and serum alpha-amylase (AA) levels in 16 healthy dogs and 31 diseased dogs using a kinetic enzyme assay to assess the stress status. The sAA and serum AA levels were significantly higher in the diseased dogs than in healthy dogs (p < 0.05), but there was no correlation between the 2 groups (r = 0.251, p = 0.089). This suggests that sAA can be useful a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Therefore, a work activity characterized by greater effort led to lower levels of α-amylase; these results were contrary to our expectation. Indeed, most recent literature data relate increased levels of α-amylase to various stress factors, such as cardiovascular risk [ 32 ] and anxiety [ 33 , 34 , 35 ]. These contrasting results could be partly explained by the time of collection; in fact, the morning collection of the salivary sample overlaps as a time span with the negative post-awakening peak.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a work activity characterized by greater effort led to lower levels of α-amylase; these results were contrary to our expectation. Indeed, most recent literature data relate increased levels of α-amylase to various stress factors, such as cardiovascular risk [ 32 ] and anxiety [ 33 , 34 , 35 ]. These contrasting results could be partly explained by the time of collection; in fact, the morning collection of the salivary sample overlaps as a time span with the negative post-awakening peak.…”
Section: Discussionmentioning
confidence: 99%
“…The sAA is another representative of SAM activation, and has been investigated in dogs. The activity of sAA increased in dogs with various diseases compared to healthy dogs [28]. Salivary immunoglobulin A (sIgA) is a proven stress biomarker in human medicine [40].…”
Section: Discussionmentioning
confidence: 99%
“…Saliva analysis has been widely used in recent stress studies because it is less invasive than blood collection and causes less stress in patients [19,27]. Similarly, various salivary biomarkers, such as cortisol and salivary alpha amylase (sAA), have been investigated in veterinary medicine [19,28]. Specifically, methods for the quantification of AVP in saliva have been validated in domestic dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, biomarkers play an important role and serve as a proxy when assessing emotion and positive well-being in animals (e.g., von Borell et al, 2007 ; Schmied et al, 2008 , 2010 ; Reefmann et al, 2009a , b ; Coulon et al, 2013 , 2015 ; Briefer et al, 2015 ; Kowalik et al, 2017 ). Heart rate (HR) ( Csoltova et al, 2017 ), heart rate variability (HRV) ( Bergamasco et al, 2010 ; Katayama et al, 2016 ; Travain et al, 2016 ), surface temperature ( Travain et al, 2015 , 2016 ; Csoltova et al, 2017 ), oxytocin ( Odendaal and Meintjes, 2003 ; Mitsui et al, 2011 ; Rehn et al, 2014 ; Nagasawa et al, 2015 ), vasopressin ( Hydbring-Sandberg et al, 2004 ; MacLean et al, 2017a , b , 2018 ; Pirrone et al, 2019 ), cortisol ( Hennessy et al, 1998 , 2006 ; Coppola et al, 2006 ; Bergamasco et al, 2010 ; Shiverdecker et al, 2013 ), and alpha-amylase ( Contreras-Aguilar et al, 2017 ; Hong et al, 2019 ) have been implemented and showed potential usefulness in indirect and noninvasive assessment of positive-emotion in dogs.…”
Section: Positive-emotion Assessment In Dogsmentioning
confidence: 99%
“…As with cortisol, measuring decreased levels of alpha-amylase, a crucial salivary enzyme ( Nater and Rohleder, 2009 ), is another noninvasive approach to test sympathetic nervous system deactivation. Salivary alpha-amylase increase in response to both acute and chronic stressors has been documented in different animal species ( Fuentes et al, 2011 ; Behringer et al, 2012 ; Fuentes-Rubio et al, 2016 ; Contreras-Aguilar et al, 2018 ), including dogs ( Contreras-Aguilar et al, 2017 ; Hong et al, 2019 ). However, other studies emphasize the involvement of the parasympathetic nervous system branch in alpha-amylase secretion ( Asking and Proctor, 1989 ; Nater and Rohleder, 2009 ; Bosch et al, 2011 ).…”
Section: Positive-emotion Assessment In Dogsmentioning
confidence: 99%